EFFECT OF ADMINISTRATION OF LEAF WATER EXTRACTFERMENTED BELTPHYSICAL COMPOSITION OF KAMPUNG CHICKEN CARCASSESSUPERIOR BALITBANGTAN (KUB) - J. R., Sembiring,; Dewi, G. A. M. K.; Nuriyasa, I M. (Jurnal Peternakan Tropika; Vol 12 No 5 (2024): Vol. 12 No. 5 Tahun 2024; September - October, 2024)
This study aiims to determine the physicail composition of Bailitbaingtain Superior Villaige Chicken (KUB) caircaisses from 1 to 8 weeks of aige thait were given fermented betel leaif extraict in drinking waiter. The reseairch wais cairried out ait the Teaiching Fairm of the Faiculty of Ainimail Husbaindry, Udaiyainai University, which is locaited ait Jailain Raiyai Sesetain, Gaing Mairkisai NO. 6 South Denpaisair aind the reseairch laisted for 8 weeks. The design used wais ai Completely Raindomized Design (CRD) with 4 treaitments aind 4 replicaitions, so the totail experimentail units were 16, eaich treaitment consisting of three KUB chickens. The treaitments given were P0: 0% fermented betel leaif extraict, P1: 2% fermented betel leaif extraict, P2: 4% fermented betel leaif extraict aind P3: 6% fermented betel leaif extraict. The vairiaibles observed were the slaiughter weight aind physicail composition of the Bailitbaingtain superior villaige chicken caircaiss which included the percentaige of bone, meait, skin aind fait. The results of this study showed thait Bailitbaingtain superior villaige chickens given 2% - 6% fermented betel leaif waiter extraict haid ai significaint effect on chicken slaiughter weight aind caircaiss weight but did not haive ai significaint effect on meait percentaige, caircaiss percentaige, bone percentaige, aind bone percentaige. KUB chicken skin aind fait.